Giant Cyst as a Dermis Fat Graft Complication in Socket Anophthalmia Post Enucleation: Poster Presentation - Case Report - Resident - Ghina Fedora; Yunia Irawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Enucleation is often performed in children diagnosed with advanced unilateral group E retinoblastoma as a primary treatment to save life. After performing enucleation, a Dermis Fat Graft (DFG) is often placed inside the socket to give volumes into the orbital cavity. A dermis fat graft hopefully will grow along with the children, promoting orbital bone development. Rare complications following dermis fat graft implant is cyst formation. The purpose is to present a case of giant orbital cyst formation in socket anophthalmia. Case Illustration : A 6 year old boy came with proptotic left socket anophthalmia with history of enucleation with DFG for retinoblastoma. On examination, we found a proptotic socket 1.5 years after enucleation. CT Scan examination revealed cyst formation on left socket anophthalmia. We did a cyst excision using cryo and implanted 16 mm acrylic implant for the socket reconstruction. Discussion : Cyst is minor complications following DFG implantation in socket anophthalmia. It’s estimated occurred in 1.5-3.8% patients. Some of the causes are gaps in between the dermis and recipient bed, epithelial island residue on DFG, or delayed conjunctivalization of the dermis. Cyst excision with careful dissection is the main management for this cases, preferably using cryo probe in order to remove the cyst in toto. Conclusion : Management for the giant cyst removal following DFG implant is a challenging task due to the recurrence possibility. Complete cyst excision and replacement of orbital implant is mandatory in order to re-establish the cosmetic appearance of the patient.